Pemikiran Pendidikan Ali bin Abi Thalib dan Relevansinya dengan Pendekatan Deep Learning Kurikulum Merdeka di MI/SD - astuti, Efi Tri (Dawuh Guru: Jurnal Pendidikan MI/SD, 2026)
This study aims to examine Ali bin Abi Thalib’s educational thought and analyze its relevance to the deep learning approach within the Merdeka Curriculum at the elementary school/madrasah ibtidaiyah level. The research employs a qualitative approach using a library research design. Data were collected from national and international journals accessed through databases such as Google Scholar, SINTA, and university journal portals, covering publications from 2020 to 2025. The findings indicate that, in terms of the nature of education, learning objectives, concept of knowledge, learning processes, the role of teachers, learners, values and character, and learning orientation, Ali bin Abi Thalib’s educational thought demonstrates strong and substantive relevance to the deep learning approach in the Merdeka Curriculum at the elementary school/madrasah ibtidaiyah level. The deep learning approach, which emphasizes meaningful, reflective, and contextual learning within the framework of meaningful learning, mindful learning, and joyful learning, aligns closely with Ali bin Abi Thalib’s views on the importance of deep understanding, moral responsibility, and education that is adaptive to the times and responsive to learners’ developmental needs.